DOI’ MENRE’ PADA MASYARAKAT BUGIS DI DESA IWOI MENGGURA KECAMATAN AERE KABUPATEN KOLAKA TIMUR - Hasniah Hasniah; Norma Norma (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
The purpose of this research is to know and to describe the reason for the high of doi’ menre’ for Bugis society in Iwoi Menggura Village and to know the way of Bugis society in setting the doi’ menre' in Iwoi Menggura Village. The technique of data collection was done by using field research method. Direct research to the field by using data collection techniques, namely: observation and in-depth interviews. In order to answer the problem required the analysis of the data. The technique of data analysis was descriptive qualitative. The analysis of data was performed since the collection of data until the end of the research. The finding of the research shows that there are several reasons underlying the high of doi 'menre' in Iwoi Menggura Village, which is social stratification of female family, the price of basic goods is more expensive, the economic status of the prospective wife, the education of the future wife, the position of the female family, the physical condition prospective wife, and the status (widow or girl). How to set the doi 'menre' is different for every family, there is a very short process and some also take a long time due to some considerations. There is even one case of marriage forced to be postponed because the male family's marriage can not able to reach the doi 'menre' that set by the female family.